ENHANCING CREATIVE THINKING SKILL IN THE HIGHER SECONDARY STUDENTS - Parmar, Dipesh; Pathak, Satish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The proposed study “Enhancing Creative Thinking Skill in The Higher Secondary Students" aims to evaluate the creative thinking abilities of higher secondary students. Study investigates impact of various interventions and strategies for enhancing creative thinking including creative thinking workshops, problem-solving exercises and collaborative projects on enhancing creative thinking skills. A random sample of 100 higher Secondary students from two school of Vadodara district were selected. Data was collected through pre and post intervention task and creative thinking test. Data was analysed by mean, SD and two tailed t-test, the finding shows that after the intervention the creative thinking skill scores of students show a significant improvement. The data analysis and interpretation can provide valuable insights into the creative thinking ability of higher secondary students. Appropriate steps can then be taken to enhance this important 21st century skill.